Inherited cardiomyopathies - Harper, A; Yavari, A; Ashrafian, H (Elsevier, 2014)
The advent of molecular genetics - fuelled by the progress in DNA sequencing technologies and publication of the landmark Human Genome Project over a decade ago - has had a major impact on our understanding of the architecture of disease, opening up the prospect of personalized medicine based upon knowledge of an individual's genetic variants. Current management of patients with inherited cardiomyopathies is starting to integrate knowledge of an individual's genomic profile together with advancements in cardiovascular imaging. This has enhanced surveillance potential for high-risk individuals and has begun to facilitate diagnosis and, to a lesser extent, appropriate risk stratification and prognostication. This review introduces the reader to the inherited cardiomyopathies (hypertrophic cardiomyopathy, arrhythmogenic cardiomyopathy and dilated cardiomyopathy) - representing the first cardiac disorders to be accurately delineated at a molecular genetic level - and provides an insight into their molecular genetic and clinical complexity.